Mozgalom a magyar nemzet védelmére az Egyesült Nemzetek Szövetségében: Munkaprogamm (II) . Movement for the Protection of the Hungarian Nation in the United Nations. Work Program (II) - Héderváry, Claire de (1962)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Movement for the Defense of the Hungarian Nation The movement's working program.